Volunteers: An Effective Medium for Delivering Therapeutic Lifestyle Interventions. Issue 4 (May 2022) - Kent, Lillian M.; Rankin, Paul M.; Morton, Darren P.; Rankin, Rebekah M.; Greenlaw, Roger L.; Englert, Heine S.
Purpose: Lifestyle modification programs have been shown to effectively treat chronic disease. The Coronary Health Improvement Program has been delivered by both paid professional and unpaid volunteer facilitators. This study compared participant outcomes of each mode in the United States. Design: Pre-/post-analysis of CHIP interventions delivered between 1999 and 2012. Setting: Professional-delivered programs in Rockford Illinois 1999-2004 and volunteer-delivered programs across North America 2005-2012. Subjects: Adults ≥21 years (professional programs N = 3158 34.3% men, mean age = 54.0 ± 11.4 years; volunteer programs N = 7115 33.4% men, mean age = 57.4 ± 13.0 years). Measures: Body mass index, blood pressure (systolic and diastolic), blood lipid profile (total cholesterol, high-density lipoprotein, triglycerides, low-density lipoprotein), and fasting plasma glucose. Analysis: Analysis of Covariance, with adjustment for age, gender, BMI change and baseline biometric and effect sizes. Results: The professional-delivered programs achieved significantly greater reductions in BMI (.4%, P < .001) and HDL (1.9%, P < .001) and the volunteer-delivered programs achieved greater reductions in SBP (1.4%, P < .001), DBP (1.1%, P < .001), TC (1.4%, P = .004), LDL (2.3%, P < .001), TG (4.0%, P = .006), and FPG (2.7%, P < .001). However, the effect size differences between the groups were minimal (Cohen's d .1-.2). Conclusions: Lifestyle modification programs have been shown to effectively treat chronic disease. The Complete Health Improvement Program (CHIP) lifestyle intervention has been delivered by both paid professional and unpaid volunteer facilitators. This study compared selected chronic disease biometric outcomes of participants in each mode in the United States. It found volunteer-delivered programs do not appear to be any less effective than programs delivered by paid professionals, which is noteworthy as volunteers may provide important social capital in the combat of chronic disease.